PROFIL COMPETITIVE ANXIETY DAN KESIAPAN PENAMPILAN SUPERIOR PADA ATLET FUTSAL MAHASISWA - Faiza Elfrisdat, - (2020)
Anxiety and performance are two important things for athletes to show good performance during the match. The purpose of this study was to determine the level of Competitive Anxiety and Superior Performance Readiness in Student Futsal Athletes. The research method used in this research is descriptive. A total of 20 male futsal athletes were students of the University of Education of Indonesia. The samples were taken using purposive sampling. The instrument used in this study was CSAI-2 (Competitive Sports Anixety Inventory) to measure the level of anxiety and several subcomponents such as cognitive anxiety, somatic anxiety, and self-confidence. And Psycologic Peak Performance to measure the performance of athletes in the field. The results of the study were analyzed using the Pearson correlation on SPSS version 25 which states that the first categorized Competitive Anxiety data is Moderate Cognitive Anxiety with 60%, moderate Somatic Anxiety with 80%, and high Self Confidence with 95%. And Superior Appearance Readiness that is moderate with a yield of 95% and a high one with a yield of 5%. Suggestions for futsal coaches and athletes to always be a form of concern in the psychological field because this can be proven to have a significant effect on athletes during the match. Keywords: Competitive Anxiety, Performance, Futsal, CSAI-2.